Techno-economic assessment of green urea production integrated with direct air capture - Ehsan Soroodan; Sanger Huang; Dia Milani; Ali Kiani; Paul Feron (Energy Conversion and Management: X)
This study evaluates the techno-economic feasibility of producing low-CO2, or ‘green urea’ at an industrial scale, powered entirely by renewable energy. Eliminating the use of fossil fuels, the green urea process integrates alkaline water electrolysers (AWE) for green hydrogen (H2) production and direct air capture (DAC) for CO2 sourcing into an industrially mature pathway using Haber-Bosch and stripping processes for ammonia (NH3) and urea synthesis, respectively. Results indicate that hydrogen production is the primary cost driver in the green urea process. Under a base-case scenario in Australia, assuming a levelised cost of electricity (LCOE) of 71 USD/MWh from solar photovoltaic (PV) and onshore wind sources, the levelised cost of green urea (LCGU) is estimated at 989 USD/tonne. Sensitivity analysis shows that ± 50 % variations in key parameters impact the LCGU by up to ± 15.3 %, with electricity price exerting the greatest influence. The study also highlights opportunities for cost reduction. Lowering the electricity price to 30 USD/MWh reduces the cost of hydrogen production to 1 USD/kg, leading to a 42 % decrease in LCGU. Additionally, the CO2 premium falls by 60 % relative to the base-case scenario. While the current cost of green urea remains relatively high, the findings underscore its potential role in derisking fertiliser supply chain and achieving significant cost reductions through advances in green hydrogen and DAC technologies.